Elemental analysis of Andrographis echioides (L.)Nees. leaves, a potential pharmaceutical plant using atomic absorption spectroscopy (AAS). - P.S, Preetha.; Kartha. A.J., Anjana (Asian Journal of Pharmaceutical Research and Development, 2021)
Andrographis echioides (L.) Nees.is a herbaceous plant belonging to the Acanthaceae family, which is widely used for traditional medicinal purposes. The present study was aimed to analyze the elemental composition in leaves of Andrographis echioides (L.) Nees. using atomic absorption spectroscopy (AAS)..A total of 12 elements Calcium, Iron, Magnesium, Manganese, Cadmium, Nickel, Sodium, Lead, Chromium, Zinc, Silver, and Copper have been analyzed quantitatively. The results showed that Calcium has the highest concentration among other elements analyzed. It shows the ability of this plant to maintain the proper functioning of cells in our body. It also plays an important role in the functioning of our nervous system. The concentration of iron and magnesium was also significant. Iron is an essential element for blood production and Magnesium play an important role in human body to maintain cholesterol levels, maintains heart rhythm and also has the capacity to converts blood sugar into energy. Andrographis echioides (L.) Nees. plant can be utilized for treating deficiencies of different essential macro and micro-nutrients for maintaining good health. The plant can be utilized for various other pharmaceutical purposes also.